UV detection on artificial uric acid using UV-Vis spectrometer - Nor Mazlee, Norazmi; Zul Rasyied, Abdul Rasat; Mazuina, Mohamad; Hadi, Manap (OMICS International, 2018)
The aim of this research work is to measure the concentration and absorption cross-section of artificial uric acid in the Ultraviolet (UV) region using UV-Vis spectrometer. The uric acid sample comes in powder form which has to be dissolved with distilled water to convert it into liquid form. Therefore, it can be placed in the cuvette for the analysis purposes. This research study was proposed to make a comparison with the previous research studies that uric acid was normally extracted from human serum as a real sample. This research study was carried out using an artificial sample of uric acid with the suspended or grits of uric acid which were not totally dissolved. These grits might be artificially assumed as crystallites which is common with Gout disease. Based on the medical perspective, crystallites normally inhibit the human joints which may cause intense pain to the human bones or tissues. In the experiment, the distilled water was used a background or reference spectrum which can be stored and automatically deducted using the Spectra suite software application. Thus, Spectra suite only measures the pure concentration and UV absorption wavelength of the uric acid through the use of the spectrometer. The absorbance data was extracted and substituted into Beer’s Lambert Law formula to calculate the value of absorption cross-section. The result shows that the value of UV absorption wavelength and absorption cross-section is really close as reported in the previous research studies. It proves that even the artificial sample of uric acid with the grits still can give a very close result. The UV absorption of uric acid was obtained at 293.99 nm by four different concentrations. The response time was successfully done in 3 seconds. The resulting curves have noise signals which can be analyzed and reduced using an averaging method to make the curve look sharper and lack of noise.